"The Cake and Custard is Good!" A Qualitative Study of Teenage Childrens' Experience of being in Prison. (17th September 2013) - Holligan, Chris
<x xml:space="preserve">Abstract</x> This qualitative study aims to uncover how young people, sentenced for violent offences, experience prison, something about which we know very little. It reports life history data from qualitative interviews with young male inmates aged 16–18 years convicted of violent assault. The findings indicate that the intrusive and inescapable challenges of incarceration are filtered through the boys' interpretations of previous critical incidents in their lives, in a way that can, it is argued, cause them additional harm. Respecting and attempting to understand the complex experiences of the participants, listening to the voices of these children, may help us to understand why a prison sentence seems to have limited impact on recidivism.